Unusual cause of mediastinal tumor: A case of calcified pericardial cyst - S M Tajdit Rahman MBBS, MS; Mofizur Rhaman Mia MBBS, MS; Mohammad Anamul Hoque MBBS, FCPS; Sanghita Banik Proma MBBS (Rare Tumors, 2023)
Pericardial cysts are rare benign intrathoracic lesions, and calcified pericardial cysts are even more uncommon. Most pericardial cysts are asymptomatic, but patients may present with chest pain, dyspnea and any complications of pericardial effusion. We present a case of a left-sided calcified pericardial cyst, highlighting its rarity and symptoms in relation to its location.